Q. 1 E4.1( 14 Votes )

Solve each of the following pairs of equations by reducing them to a pair of linear equation.




Answer :

and

Let = p and = q


5p – 2q = -1 ….I


15p + 7q = 10 ….II


Multiply Eq. I by 3 and subtract eq. II


15p – 6q = -3


-15p - 7q = -10


-13q = -13


q = 1


substitute the value of q in Eq. I


5p – 2(1) = -1


5p = - 1 + 2


5p = 1


p =


But, 5 = x + y …III


1 = x – y y = x – 1


Substitute value of y in eq. III


x + x – 1 = 5


2x = 6


x = 3


y = 3 – 1 = 2


x = 3 and y = 2


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.